Preoperative and postoperative optimisation of patients undergoing thyroid surgery: a multicentre quality improvement project at Barts Health NHS Trust - Jahangir Ahmed; Deepak Chandrasekharan; Ghassan Alusi; Matt Lechner; Mona Waterhouse; Kalpita Majumdar; Oscar Emanuel; Gulwish Moghul; Salman Ashraf; Tiarnan Magos; Zi Wei Liu; Margaret Crutchlow; et al. (BMJ Open Quality)
Hypocalcaemia following thyroid surgery can occur in up to 38% of patients. With over 7100 thyroid surgeries performed in 2018 in the UK, this is a common postoperative complication. Undertreated hypocalcaemia can result in cardiac arrhythmias and death. Preventing adverse events from hypocalcaemia requires preoperative identification and treatment of at-risk patients with vitamin D deficiency, timely recognition of postoperative hypocalcaemia and prompt appropriate treatment with calcium supplementation. This project aimed to design and implement a perioperative protocol for prevention, detection and management of post-thyroidectomy hypocalcaemia. A retrospective audit of thyroid surgeries (n=67; October 2017 to June 2018) was undertaken to establish baseline practice of (1) preoperative vitamin D levels assessment, (2) postoperative calcium checks and incidence of postoperative hypocalcaemia and (3) management of postoperative hypocalcaemia. A multidisciplinary team approach following quality improvement principles was then used to design a perioperative management protocol with all relevant stakeholders involved. After dissemination and implementation, the above measures were reassessed prospectively (n=23; April–July 2019). The percentage of patients having their preoperative vitamin D measured increased from 40.3% to 65.2%. Postoperative day-of-surgery calcium checks increased from 76.1% to 87.0%. Hypocalcaemia was detected in 26.8% of patients before and 30.43% of patients after protocol implementation. The postoperative component of the protocol was followed in 78.3% of patients. Limitations include low number of patients which precluded from analysis of the impact of the protocol on length of stay. Our protocol provides a foundation for preoperative risk stratification and prevention, early detection and subsequent management of hypocalcaemia in thyroidectomy patients. This aligns with enhanced recovery protocols. Moreover, we offer suggestions for others to build on this quality improvement project with the aim to further advance the perioperative care of thyroidectomy patients.